Soft Mechanics: Contrast Agent Incorporation into Silicone Enables Real‐Time Flow‐Structure Analysis of Mammalian Vein‐Inspired Soft Pumps (Adv. Funct. Mater. 14/2015). (April 2015) - Loepfe, Michael; Schumacher, Christoph M.; Burri, Cornelia H.; Stark, Wendelin J.
Abstract : On page 2129, W. J. Stark and co‐workers demonstrate a new type of mammalian vein‐inspired soft silicone liquid pump, which is based on lost‐wax casting of 3D printed injection molds. By functionalizing the material with contrast agents, inner workings can be visualized in real‐time by the use of medical ultrasonography. The figure shows this visualization process, performed by an untrained user, namely an engineer.